2010
DOI: 10.1242/jcs.064279
|View full text |Cite
|
Sign up to set email alerts
|

Reversible transdifferentiation of blood vascular endothelial cells to a lymphatic-like phenotype in vitro

Abstract: SummaryBlood vascular cells and lymphatic endothelial cells (BECs and LECs, respectively) form two separate vascular systems and are functionally distinct cell types or lineages with characteristic gene expression profiles. Interconversion between these cell types has not been reported. Here, we show that in conventional in vitro angiogenesis assays, human BECs of fetal or adult origin show altered gene expression that is indicative of transition to a lymphatic-like phenotype. This change occurs in BECs underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 39 publications
(21 reference statements)
2
26
0
Order By: Relevance
“…However, upon assessment of EC potential after serial passages, we observed that sorted and matured ECs lost some VEcad expression by passage 4, warranting future work that will examine means to retain endothelial potential over numerous passages via media or culture optimization. These findings are in agreement with a previous study, which also demonstrated loss of vascular EC marker expression from mature, fully differentiated ECs (i.e., human umbilical vein ECs) and their subsequent transdifferentiation toward lymphatic ECs in vitro [32]. Moreover, previous studies report that PSCderived ECs lose their endothelial potential over serial passaging, perhaps owing to the notion that these derivatives may still exhibit some plasticity [33].…”
Section: Discussionsupporting
confidence: 93%
“…However, upon assessment of EC potential after serial passages, we observed that sorted and matured ECs lost some VEcad expression by passage 4, warranting future work that will examine means to retain endothelial potential over numerous passages via media or culture optimization. These findings are in agreement with a previous study, which also demonstrated loss of vascular EC marker expression from mature, fully differentiated ECs (i.e., human umbilical vein ECs) and their subsequent transdifferentiation toward lymphatic ECs in vitro [32]. Moreover, previous studies report that PSCderived ECs lose their endothelial potential over serial passaging, perhaps owing to the notion that these derivatives may still exhibit some plasticity [33].…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, a recent lineage-tracing analysis shows that PDGFRβ-positive endothelium contributes to the CLV formation during embryonal development [14], implying that upon severe tissue injury, blood endothelial cells acquire the lymphatic endothelial cell phenotype. Such endothelial cell plasticity has been previously described in cultured cells and for the tumor vasculature [4345]. …”
Section: Resultsmentioning
confidence: 78%
“…Endothelial growth medium-EGM2 (C22011; PromoCell, Birmingham, UK) with supplements was used as culture medium for HuVECs according to the manufacturer's protocols. Murine perivascular cells (PVC) were isolated as previously described and used between passages 32 and 38 (35). Pericytes were routinely incubated in Dulbecco's modified Eagle's medium (DMEM) containing 10% fetal bovine serum (FBS).…”
Section: Methodsmentioning
confidence: 99%